Cerebrovascular autoregulation in preterm fetal growth restricted neonates (2019)
Objective To investigate the effect of fetal growth restriction (FGR) on cerebrovascular autoregulation in preterm neonates during the first 3 days of life. Design Case-control study. Setting Neonatal intensive care unit of the Wilhelmina Children's Hospital, The Netherlands. Patients 57 FGR (birth weight less than 10th percentile) and 57 appropriate for gestational age (AGA) (birth weight 20th-80th percentiles) preterm neonates, matched for gender, gestational age, respiratory and blood pressure support. Methods The correlation between continuously measured mean arterial blood pressure and regional cerebral oxygen saturation was calculated to generate the cerebral oximetry index (COx). Mean COx was calculated for each patient for each postnatal day. The percentage of time with impaired autoregulation (COx>0.5) was also calculated. Results FGR neonates had higher mean COx values than their AGA peers on day 2 (0.15 (95% CI 0.11 to 0.18) vs 0.09 (95% CI 0.06 to 0.13), p=0.029) and day 3 (0.17 (95% CI 0.13 to 0.20) vs 0.09 (95% CI 0.06 to 0.12), p=0.003) of life. FGR neonates spent more time with impaired autoregulation (COx value >0.5) than controls on postnatal day 2 (19% (95% CI 16% to 22%) vs 14% (95% CI 12% to 17%), p=0.035) and day 3 (20% (95% CI 17% to 24%) vs 15% (95% CI 12% to 18%), p=0.016). Conclusion FGR preterm neonates more frequently display impaired cerebrovascular autoregulation compared with AGA peers on days 2 and 3 of life which may predispose them to brain injury. Further studies are required to investigate whether this impairment persists beyond the first few days of life and whether this impairment is linked to poor neurodevelopmental outcome. © Author(s) (or their employer(s)) 2019.